Control of PbI2 nucleation and crystallization: towards efficient perovskite solar cells based on vapor-assisted solution process. (13th April 2018) - Yang, Chongqiu; Peng, Yanke; Simon, Terrence; Cui, Tianhong
Abstract: Perovskite solar cells (PSC) have outstanding potential to be low-cost, high-efficiency photovoltaic devices. The PSC can be fabricated by numerous techniques; however, the power conversion efficiency (PCE) for the two-step-processed PSC falls behind that of the one-step method. In this work, we investigate the effects of relative humidity (RH) and dry air flow on the lead iodide (PbI2 ) solution deposition process. We conclude that the quality of the PbI2 film is critical to the development of the perovskite film and the performance of the PSC device. Low RH and dry air flow used during the PbI2 spin coating procedure can increase supersaturation concentration to form denser PbI2 nuclei and a more suitable PbI2 film. Moreover, airflow-assisted PbI2 drying and thermal annealing steps can smooth transformation from the nucleation stage to the crystallization stage.